Reflections of teacher’s training in the supervised internship of observation in English language: challenges and possibilities in the "postmethod" era - RAMOS, Evellyn Rayane da Silva (2023)
This article is an experience report of observation in the supervised high school internship . Th e study was based on the need to investigate the teaching practice in a public school. The reflections made during the internship were coupled with the postmethod perspectives of English language teaching. It general aimed to investigate the teaching practice in a public school, and for specific objectives to reflect how the theories learned in university converge with teaching practice observed in the internship. The methodology used was qualitative and the techniques were observations and semi-structured interviews. The result we noticed while observing the classes is that although the teacher has a plan to organize the classes, there are many obstacles that influence their practice, such as the little class time given to the subject, overcrowding in the classrooms, the challenges of teaching students with special needs, etc. All of this makes it difficult for the teacher to develop more attractive classes with a postmethod perspective in mind. This study showed us the importance of getting to know in practice the challenges of teaching English in public school, and this experience is of great relevance to the education of the student-teacher.